Batteries: 3D Hyperbranched Hollow Carbon Nanorod Architectures for High‐Performance Lithium‐Sulfur Batteries (Adv. Energy Mater. 8/2014). Issue 8 (June 2014) - Chen, Shuangqiang; Huang, Xiaodan; Liu, Hao; Sun, Bing; Yeoh, Waikong; Li, Kefei; Zhang, Jinqiang; Wang, Guoxiu
<x xml:space="preserve">Abstract</x> Hyperbranched, hollow carbon nanorod encapsulated sulfur composites are synthesized using a chemical vapor deposition (CVD) method and used as the cathode materials in lithium‐sulfer batteries. As reported by Guoxiu Wang and co‐workers in article number 1301761, the sulfur composite cathodes deliver high specific capacity, excellent high rate capability, and extended cycle life. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>